Thermal Shock Effect on Strength Loss Properties of Rock Materials: An Experimental Study on Thermal Fatigue Durability - Eren Kömürlü (Doğal Afetler ve Çevre Dergisi)
Four different types of rock materials from Eastern Black Sea Region of Turkey were investigated to determine their change in porosity as well as the degree of cracking, fracturing, disintegration and strength loss under heating-cooling cycles with variations in temperatures up to 300 Co. Cooling time and thermal strains of the rock specimens were also determined in this study. Totally, sixty rock core samples were tested to evaluate their physico-mechanical and mechanical properties. Thermal cycling was found to lead for increase in the porosity of the rocks, making new cracks, particle disintegration for two types of tested rocks and considerable losses in uniaxial compressive strength values of all the rock materials tested in this study. The purpose of this study is to investigate immediate changes in temperature values rather than step by step heating up to a target temperature. For instance, rock samples were directly put in 250 oC stove from a -50 oC cabin in the last and fifth thermal cycling. After the heating process, specimens were cooled in water and air. This study aims to be a usable reference to establish a thermal change procedure and improve a new testing method for determination of thermal fatigue durability of rock materials.